A Case of Gallstones Causing Pelvic Pain. (19th July 2021) - Drahman, Aizat; Arulpragasam, Kaushi; Leibenson, Lilach; Sardelic, Frank
Abstract : Introduction. Assessing abdominal pain, particularly in women of reproductive age, requires thorough history taking, clinical examination, and investigations to obtain an accurate diagnosis. Both surgical and gynecological causes need to be considered, particularly previous relevant surgical history. Presentation of case. We report a case of pelvic pain secondary to multiple gallstones found within the pelvic cavity postlaparoscopic cholecystectomy. Thorough investigations have been conducted without any obvious cause found. The pain was debilitating and largely affecting the patient's quality of life. Therefore, decision to perform diagnostic laparoscopy and gallstones was found all over pelvic cavity and retrieved. Her pain resolved post operatively. Conclusions. Gallbladder perforation and stone spillage are the most common complications of laparoscopic cholecystectomy that arise during the removal and dissection of gallbladder and can cause significant morbidity if not managed early, especially retrieval of the stones intraoperatively. Therefore, patient with history of previous cholecystectomy with stone spillage presenting with undifferentiated abdominal pain and early diagnostic laparoscopy should be considered.